2016
DOI: 10.1002/2016gl068668
|View full text |Cite
|
Sign up to set email alerts
|

Ephemerality of discrete methane vents in lake sediments

Abstract: Methane is a potent greenhouse gas whose emission from sediments in inland waters and shallow oceans may both contribute to global warming and be exacerbated by it. The fraction of methane emitted by sediments that bypasses dissolution in the water column and reaches the atmosphere as bubbles depends on the mode and spatiotemporal characteristics of venting from the sediments. Earlier studies have concluded that hot spots—persistent, high‐flux vents—dominate the regional ebullitive flux from submerged sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…In all these environments, especially shallow waters, the total gas pressure can exceed the ambient hydrostatic pressure, resulting in the formation of CH 4 bubbles in the sediment (Maeck et al, ). Transport through ebullition is faster than through diffusion, although ebullition can also be highly episodic (Scandella et al, ), allowing CH 4 to bypass the geochemical barrier of oxygen and SO 4 2− (Figure ) (DelSontro et al, ). In the intertidal zone in estuaries and in mangroves, CH 4 may also be transferred directly from sediments to the atmosphere (Borges & Abril, ).…”
Section: Marine and Freshwater Systemsmentioning
confidence: 99%
“…In all these environments, especially shallow waters, the total gas pressure can exceed the ambient hydrostatic pressure, resulting in the formation of CH 4 bubbles in the sediment (Maeck et al, ). Transport through ebullition is faster than through diffusion, although ebullition can also be highly episodic (Scandella et al, ), allowing CH 4 to bypass the geochemical barrier of oxygen and SO 4 2− (Figure ) (DelSontro et al, ). In the intertidal zone in estuaries and in mangroves, CH 4 may also be transferred directly from sediments to the atmosphere (Borges & Abril, ).…”
Section: Marine and Freshwater Systemsmentioning
confidence: 99%
“…Comas and Wright [] observed bubbles released from methane‐generating peat with a downward looking camera both in situ and in a laboratory sample, but their focus was on quantifying the temporal variability in ebullition, rather than understanding the spatial component of interest here. Interestingly, that study found a positive correlation between atmospheric pressure and the ebullitive flux, compared with the majority of studies, which find that ebullition is triggered by falling atmospheric pressure [ Mattson and Likens , ; Fechner‐Levy and Hemond , ; Tokida et al , ; Scandella et al , ; Varadharajan and Hemond , ; Yvon‐Durocher et al , ; Scandella et al , ], among other factors. Further experiments on wetland sediments have demonstrated triggering of ebullition with ebbing and flowing tides but did not detect the release of individual bubbles or quantify the spatial variability in ebullition [ Chen and Slater , ].…”
Section: Introductionmentioning
confidence: 71%
“…However, at least in some settings, the spatial structure of distant methane vents is ephemeral. In a record of sonar‐detected ebullition in Upper Mystic Lake (UML), MA, a characteristic spatial structure of apparently discrete seeps was observed over periods up to 1 day in duration, but over longer periods the occurrence of spatially independent venting made the pattern indistinguishable from a completely spatially random process [ Scandella et al , ]. Other studies on the UML, a dimictic, eutrophic kettle lake north of Boston, MA, include a 4 month record of ebullition from five surface‐moored bubble traps that showed surprising synchronicity in hydrostatically triggered ebullition episodes, despite the sensors' being located over water depths ranging from 9 to 25 m [ Scandella et al , ; Varadharajan and Hemond , ; Delwiche et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite the bubble-sediment material system existing in an apparently stable, time-independent state, the system is not actually in its lowest energy state. A small increase in applied force can lead to a number of different responses from no motion of the bubble to a large jump and removal of the bubble from the sediment matrix (Scandella et al, 2011(Scandella et al, , 2016.…”
Section: Emission Uncertainty and Self-organized Criticalitymentioning
confidence: 99%